Evaluating a virtual learning environment in the context of its community of practice - Rachel Ellaway; David Dewhurst; Hamish McLeod (Association for Learning Technology, 2006)
The evaluation of virtual learning environments (VLEs) and similar applications has, to date, largely consisted of checklists of system features, phenomenological studies or measures of specific forms of educational efficacy. Although these approaches offer some value, they are unable to capture the complex and holistic nature of a group of individuals using a common system to support the wide range of activities that make up a course or programme of study over time. This paper employs Wenger's theories of ‘communities of practice' to provide a formal structure for looking at how a VLE supports a pre-existing course community. Wenger proposes a Learning Architecture Framework for a learning community of practice, which the authors have taken to provide an evaluation framework. This approach is complementary to both the holistic and complex natures of course environments, in that particular VLE affordances are less important than the activities of the course community in respect of the system. Thus, the VLE's efficacy in its context of use is the prime area of investigation rather than a reductionist analysis of its tools and components. An example of this approach in use is presented, evaluating the VLE that supports the undergraduate medical course at the University of Edinburgh. The paper provides a theoretical grounding, derives an evaluation instrument, analyses the efficacy and validity of the instrument in practice and draws conclusions as to how and where it may best be used.